2009
DOI: 10.1097/nmd.0b013e3181a208af
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Diagnosis and Antiretroviral Adherence Among Adolescent Medicaid Beneficiaries Diagnosed With Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome

Abstract: Research on adults with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) has suggested that psychiatric and substance abuse comorbidities are prevalent in this population, and that these may sometimes be associated with use of antiretroviral therapy (ART) and adherence. For adolescents with HIV/AIDS, much less is known about patterns of mental health comorbidity, and even fewer data are available that compare them to socioeconomically comparable youth without HIV/AIDS. Using medical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…21 Emotional and behavioral problems, including depression, conduct problems, and alcohol use have been associated with nonadherence in older adolescents and adults with HIV infection. 13,[22][23][24] Although there is evidence suggesting emotional and behavioral problems are related to adherence in children with other chronic illnesses, 25 the relationship between such problems and adherence in children with HIV disease is not well-described. Clarifying this relationship is critical since emotional and behavioral problems in the context of chronic illness may reduce the ability to take medications as directed and affect a youth's assumption of responsibility for this important health maintenance behavior.…”
Section: Introductionmentioning
confidence: 98%
“…21 Emotional and behavioral problems, including depression, conduct problems, and alcohol use have been associated with nonadherence in older adolescents and adults with HIV infection. 13,[22][23][24] Although there is evidence suggesting emotional and behavioral problems are related to adherence in children with other chronic illnesses, 25 the relationship between such problems and adherence in children with HIV disease is not well-described. Clarifying this relationship is critical since emotional and behavioral problems in the context of chronic illness may reduce the ability to take medications as directed and affect a youth's assumption of responsibility for this important health maintenance behavior.…”
Section: Introductionmentioning
confidence: 98%
“…Mental health problems co-occur with suboptimal adherence [11]. Behavioral impairment [12], diagnosis of depression [13] or anxiety, or conduct disorder [12,14] have been associated with non-adherence, although findings have been mixed [1517]. …”
Section: Introductionmentioning
confidence: 99%
“…In two longitudinal studies of adherence in youth with PHIV, one (n=138) showed no association between emotional problems and non-adherence [17], another (n=108) did not evaluate psychiatric conditions [19]; neither evaluated predictors of becoming non-adherent. Almost all studies examining mental health and ARV adherence have either been cross-sectional [12,1416], focused on youth with non-perinatally-acquired HIV [13] or did not distinguish between HIV acquisition modes [14], used one ARV adherence measure [12, 14, 1617], or relied on psychiatric information from claims or medical records [1416]. …”
Section: Introductionmentioning
confidence: 99%
“…IMDs are associated with psychological distress (Musisi and Kinyanda, 2009), impaired quality of life, and non-adherence to ART (Walkup et al, 2009; Malee et al, 2011). In addition, patients with IMDs have higher mortality rates than have the general population (Cuijpers and Smit, 2002; Colton and Manderscheid, 2006; Ahmadi et al, 2011; Druss et al, 2011).…”
Section: Introductionmentioning
confidence: 99%